Aspectos fármaco-epidemiológicos de idosos atendidos em um hospital escola - RESENDE, Karina Dias (2022)
The proportion of people aged 60 years or older rapidly grows throughout the world and with human aging organic changes arise, along with appearance of diseases and higher susceptibility to them. Consequently, there has been an increase on the consumption of medicines, which predispose to more common pharmacologic interactions or various adverse reactions, with potencially lethal effects to elderly people. Therefore, an observational, descriptive, transversal type study regarding the epidemiological aspects and polipharmacy was carried out in a group of elderly people receiving internal medicine outpatient care at Fundação Santa Casa de Misericórdia do Pará, in Belém, from April 15th through July 15th 2005. The sample group was comprised of men and women, with age ranging from 60 to 89 years old, who had medical records at the aforementioned hospital. Patients underwent a questionnaire-based interview concerning analysis of their medical records, medical prescription and general information about their medicine. The variables were descriptively analysed as proportion and absolute numbers, being presented by means of tables and graphics produced utilizing Microsoft® Office Excel 2003 software. The analysis of probable differences between these proportions, along with exact Clopper Pearson test and associations of these variables (Chi-squared test) were calculated with the aid of Stats Direct version 2.2.3 software, adopting a p value < 0,05 for the rejection of null hypothesis, and marking meaninful values with an asterisk. The fact that the number of interviewed women was higher than the number of men did not produce any significant statistical differences. The mean age was 70,8 years old, most patients were married, residents of Belém, born in the state of Pará, having low education backgrounds and being already retired, with a high number of former smokers and alcohol consumers. A significant rate of the patients (11,05%) did not use the prescribed medicines and 61,3% did not need care for medicine administration. The use of polipharmacy was verified in 33,1% of the patients. Cardiovascular diseases, followed by endocrine diseases, were the most frequent comorbidities, while antihypertensive agents were the most prescribed medicines. It was of great relevance to study the pharmaco epidemological aspects of elderly people cared for in the referred University Hospital, and then, from the obtained data, to begin healthcare promotion and disease prevention measures, to stimulate training and continuous update for geriatrics and gerontology healthcare professionals, aiming to have them able to diagnose and treat properly, with consequent avoidance of iatrogenic actions.